Cutaneous leishmaniosis due to Leishmania mexicana in a cat treated with cryotherapy. Issue 5 (29th May 2022) - Mendoza, Yeimar; Colmenares, Alegria; Hernández‐Pereira, Carlos E.; Shaban, Maryia V.; Mogollón, Alexander; Morales‐Panza, R.J.; Suarez‐Alvarado, Maria Jose; Sordillo, Emilia M.; Kato, Hirotomo; Paniz‐Mondolfi, Alberto E.
Abstract: We report the novel use of cryosurgery to treat cutaneous feline leishmaniosis (FeL) in a domestic cat from mid‐western Venezuela. Amastigotes, evident by microscopy in aspirates from the nodular, erythematous nose lesions, were identified as Leishmania mexicana by cytochrome b gene sequence analysis. Lesions resolved completely without relapse after 14 months. Abstract : We report the novel use of cryosurgery to treat cutaneous feline leishmaniosis (FeL) in a domestic cat from mid‐western Venezuela. Amastigotes, evident by microscopy in aspirates from the nodular, erythematous nose lesions, were identified as Leishmania mexicana by cytochrome b gene sequence analysis. Lesions resolved completely without relapse after 14 months. Résumé: Nous décrivons une nouvelle utilisation de la cryochirurgie pour traiter la leishmaniose féline cutanée (FeL) chez un chat domestique du centre‐ouest du Venezuela. Les amastigotes, observés par microscopie dans les cytoponctions des lésions nodulaires et érythémateuses du nez, ont été identifiés comme Leishmania mexicana par analyse de la séquence du gène du cytochrome b. Les lésions ont complètement disparu sans rechute après 14 mois. Resumen: Describimos el uso novedoso de la criocirugía para tratar la leishmaniosis cutánea felina (FeL) en un gato doméstico del medio oeste de Venezuela. Los amastigotes, evidentes por microscopía en los aspirados de las lesiones nasales nodulares eritematosas, se identificaron como Leishmania mexicana mediante el análisis de la secuencia del gen del citocromo b. Las lesiones se resolvieron completamente sin recidiva tras 14 meses. Zusammenfassung: Wir berichten über den neuen Einsatz von Kryotherapie zur Behandlung kutaner feliner Leishmaniose (FeL) bei einer Hauskatze im Mittel‐Westen von Venezuela. Amastigoten, die mittels Mikroskopie in Aspiraten der knotigen, erythematösen Nasenveränderungen gezeigt wurden, konnten mittels b Gen Sequenzierungsanalyse als Leishmania m exicana identifiziert werden. Die Läsionen verschwanden völlig und traten in den nächsten 14 Monaten nicht wieder auf. 要約: ベネズエラ中西部の飼い猫に発生したネコ・リーシュマニア症 (FeL) の治療に凍結手術が使用されたことを報告する。鼻の結節性紅斑病変から採取した吸引液を顕微鏡で観察した結果、アマスティゴートはチトクロームb遺伝子配列解析によりLeishmania mexicanaと同定された。病変は14カ月後に再発することなく完全に治癒した。 摘要: 我们报告了使用冷冻手术的新用途, 给委内瑞拉中西部的一只家猫治疗皮肤利什曼病(FeL)。结节性、红斑性鼻病变的抽吸物, 在显微镜下明显可见无鞭毛体, 经细胞色素b基因序列分析鉴定为墨西哥利什曼原虫。14个月后病变完全消退, 无复发。 Resumo: Neste estudo, relatamos a utilização inédita de criocirurgia para tratar leishmaniose felina cutânea (FeL) em um gato doméstico no centro‐oeste da Venezuela. Amastigotas, evidentes à microscopia de aspirados da lesão nodular e eritematosa na região nasal, foram identificadas como Leishmania Mexicana por sequenciamento do gene do citocromo b . As lesões se resolveram completamente sem recidiva após 14 meses.